THE ROLE OF ACCOUNTS IN THE ADMINISTRATION OF THE FEDERAL GOVERNMENT. - Bartelt, E. F. (The Accounting Review, 1942)
Abstract In discussing the role of accounts in the administration of the affairs of the United States Government, the author talks about the history and development of accounts and the relation of Federal accounting to business accounting. It is indeed encouraging that the President of the United States and the Director of the U.S. Bureau of the Budget are committed to a comprehensive program of placing the accounts of the Federal Government upon a sound basis, which would compare favorably with those of commerce and industry. It is the author's fervent hope that the program will so commend itself to the U.S. Congress during the coming session that the Legislative branch of the Government will give its support and encouragement to those officers in the Executive branch who are desirous of providing the Congress and the American people with more informative over-all financial statements relating to the operations and condition of the Government. The author commends to readers thoughtful consideration a careful examination of the basic principles prescribed in Executive Order No. 8512, and would welcome their suggestions with respect to their application to the accounting and reporting procedures of the Federal Government.